Voices of South Asian Women: Immigration and Mental Health - Ahmad, Farah; Shik, Angela; Vanza, Reena; Cheung, Angela M.; George, Usha; Stewart, Donna E. (Women & Health, 2005)
Purpose: This qualitative research aimed to elicit experiences and beliefs of recent South Asian immigrant women about their major health concerns after immigration. Methods: Four focus groups were conducted with 24 Hindi-speaking women who had lived less than five years in Canada. The audiotaped data were transcribed, translated, and analyzed by identification of themes and subcategories. Results: Mental health (MH) emerged as an overarching health concern with three major themes, i.e., appraisal of the mental burden (extent and general susceptibility), stress-inducing factors, and coping strategies. Many participants agreed that MH did not become a concern to them until after immigration. Women discussed their compromised MH using verbal and symptomatic expressions. The stress-inducing factors identified by participants included loss of social support, economic uncertainties, downward social mobility, mechanistic lifestyle, barriers in accessing health services, and climatic and food changes. Women's major coping strategies included increased efforts to socialize, use of preventative health practices and self-awareness. Conclusion: Although participant women discussed a number of ways to deal with post-immigration stressors, the women's perceived compromised mental health reflects the inadequacy of their coping strategies and the available resources. Despite access to healthcare providers, women failed to identify healthcare encounters as opportunities to seek help and discuss their mental health concerns. Health and social care programs need to actively address the compromised mental health perceived by the studied group.
Keywords: amériques; asie; asie du sud; canada; charge mentale; cours; discipline; femmes immigrantes; médecine; régions géographiques; santé; sciences; soc1061; stress post immigration; thématiques

A new Vision for advancing our movement for reproductive health, reproductive rights and reproductive justice - Asian Communities for Reproductive Justice (Asian Communities for Reproductive Justice, 2005)
Forward Together’s (then Asian Communities for Reproductive Justice or ACRJ) groundbreaking analysis of the framework and vision for reproductive justice, described by organizations and funders as revelatory and pivotal to the field.
Keywords: amériques; approches et analyses; asie; droits des femmes*; femmes* asiatiques; femmes* de couleur; inégalités; justice reproductive; justice sociale; militance; racisme; ressource en ligne; régions géographiques; santé; santé reproductive; sexisme; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; états-unis

La démocratie et le statut des femmes au Liban - Bdeir, Leila (Université du Québec à Montréal, 2005)
Keywords: IREF; approches et analyses; asie; discipline; femmes* politiques; liban; militance; mouvements féministes; mémoires/thèses; régions géographiques; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques

Quand les femmes écrivent la guerre : transformation du genre et du monde dans Les hommes qui marchent de Malika Mokeddem et Iran, les rives du sang de Fariba Hachtroudi - Bélanger, Marie-Ève (Université du Québec à Montréal, 2005)
Keywords: 1900-1999; 1990-1999; IREF; afrique; algérie; asie; discipline; guerre; iran; mémoires/thèses; périodes historiques; régions géographiques; thématiques; violences; écriture des femmes*; études littéraires